The Impact of Hippotherapy on Motor Function in Children with Cerebral Palsy - Pyziolek, Marta; Chmura, Katrzyna; Zimnoch, Barbara; Rendaszka, Katarzyna; Kowalska, Katarzyna; Bonarska, Marta; Kwaśniewska, Paulina; Stróżna, Małgorzata; Najbar, Joanna Monika; Ostrowska, Sandra (Quality in Sport, 2025)
Background. Cerebral palsy (CP) is a group of disorders resulting from permanent damage to the central nervous system, typically occurring during the prenatal, perinatal, or early postnatal period. It is one of the leading causes of physical disability in children and is commonly associated with impaired motor development, muscle tone abnormalities, and postural control deficits. In addition to conventional physiotherapy, alternative therapeutic approaches are increasingly being incorporated into rehabilitation programs. One such method is hippotherapy – a form of movement-based therapy utilizing the three-dimensional motion of a horse to stimulate neuromotor functions. Aim. The aim of this review is to analyze current research findings on the impact of hippotherapy on motor function development in children with cerebral palsy and to assess its therapeutic value. Material and methods. This paper presents a literature review based on scientific articles selected from databases such as PubMed and Google Scholar, focusing on studies that examined motor outcomes in children with CP undergoing hippotherapy. Results. The literature confirms that hippotherapy can lead to significant improvements in balance, coordination, postural stability, and general motor functions in children with cerebral palsy. It is also well tolerated by patients and increases their motivation for further therapy. Conclusions. Hippotherapy is an effective adjunctive intervention in the rehabilitation of children with cerebral palsy. Its incorporation into therapeutic programs may enhance motor outcomes and improve the overall quality of life. Further research is recommended to refine protocols and confirm long-term benefits.